Anabolic response to essential amino acid plus whey protein composition is greater than whey protein alone in young healthy adults. Issue 1 (10th February 2020) - Park, Sanghee; Church, David D.; Azhar, Gohar; Schutzler, Scott E.; Ferrando, Arny A.; Wolfe, Robert R.
Abstract: Background: We have determined the acute response of protein kinetics to one or two servings (6.3 g and 12.6 g) of a proprietary composition containing free-form essential amino acids (EAA) (3.2 g EAA per serving) and whey protein (2.4 g per serving), as well as the response to consumption of a popular whey-based protein supplement (Gatorade Recover) (17 g; 12.6 g protein). Methods: Whole-body rates of protein synthesis, breakdown and net balance (taken to be the anabolic response) were determined using primed-constant infusions of 2 H5 -phenylalnine and 2 H2 -tyrosine. Muscle protein fractional synthetic rate (FSR) was also determined with the 2 H5 -phenylalanine tracer. Results: Plasma EAA levels increased following consumption of all beverages, with the greatest response in the high-dose EAA/protein composition. Similarly, the increase in net balance between whole-body protein synthesis and breakdown was greatest following consumption of the high-dose EAA/protein composition, while the low-dose EAA/protein composition and Gatorade Recover induced similar increases in net balance. When the net balance response was normalized for the total amount of product given, the high- and low-dose EAA/protein beverages were approximately 6- and 3-fold more anabolic than the Gatorade Recover, respectively. The greater anabolic response to the EAA/protein composition was due to greater increases in whole-body protein synthesis with both doses, and a markedly greater suppression of whole-body protein breakdown in the high-dose group. Muscle protein FSR after beverage consumption reflected changes in whole-body protein synthesis, with the larger EAA/protein dose significantly increasing FSR. Conclusion: We conclude that a composition of a balanced EAA formulation combined with whey protein is highly anabolic as compared to a whey protein-based recovery product, and that the response is dose-dependent. Trial registration: ClinicalTrials.gov Identifier: NCT03502941 . This trial was registered on April 19, 2018.